Prevalence of Plasmid-Mediated Determinants With Decreased Susceptibility to Azithromycin Among Shigella Isolates in Anhui, China - Liu, Yanyan; Li, Hongru; Lv, Na; Zhang, Yalong; Xu, Xihai; Ye, Ying; Gao, Yufeng; Li, Jiabin (Frontiers in Microbiology, 2020)
Objective: The aims of this study were to describe azithromycin (AZM) susceptibility patterns among Shigella isolates in Anhui, China and identify predictors of resistance with mobile element-mediated genes. Methods: A total of 517 non-duplicate Shigella isolates (449 S. flexneri and 68 S. sonnei) were collected in the Anhui Province of China from September 2011–September 2015, and screened for the plasmid-mediated genes of decreased susceptibility to AZM (DSA), using polymerase chain reaction amplification and sequencing. Conjugation experiments and pulsed-ﬁeld gel electrophoresis were conducted for all mphA-positive DSA isolates. Results: The DSA rate for 449 S. flexneri isolates was 33.6%, compared with 39.7% for 68 S. sonnei isolates. Among 161 DSA S. ﬂexneri isolates, 93 (57.8%) carried the mphA gene. Among 27 DSA S. sonnei isolates, 11 (40.7%) carried the mphA gene. However, other plasmid-mediated DSA genes were not found in these isolates. A total of 89 transconjugants (95.7%) were obtained from 93 mphA-positive S. flexneri isolates through conjugation, and 10 transconjugants (90.9%) were obtained from 11 mphA-positive S. sonnei isolates. Furthermore, the minimum inhibitory concentrations (MICs) of AZM among 89 S. flexneri transconjugants ranged from 4 to 128 µg/mL, with an MIC50 of 8 µg/mL and MIC90 of 32 µg/mL. The MICs of AZM among 10 S. sonnei transconjugants ranged from 4 to 256 µg/mL, with an MIC50 of 8 µg/mL and MIC90 of 64 µg/mL. Thirteen clusters were found for mphA-positive S. flexneri, and five clusters were found for mphA-positive S. sonnei. Furthermore, 10 homologous isolates among 13 mphA-positive S. flexneri isolates with high-level DSA were from Sixian county and were multidrug-resistant strains. Of the 10 homologous S. flexneri isolates, eight were from children (≤ 5 years old), and two from the elderly (> 60 years old). Conclusions: Our study demonstrates that the DSA for Shigella isolates was severe, and the plasmid-mediated mphA gene was the most common macrolide resistance gene detected in Shigella isolates collected in Anhui, China. The mphA-positive S. flexneri isolates with high-level DSA facilitated clonal spread in children and the elderly. This finding is noteworthy and warrants further study.